O efeito das ações mediadoras e o papel das práticas de leitura e escrita no processo de alfabetização acadêmica do aluno com deficiência da UFPB - Farias, Diana Ribeiro Guimarães (2021)
The practices of inclusion in the teaching environment must be thought by the community and naturalized as an ethical responsibility. To this end, it is important to listen to the voices of students with disabilities, in order to plan adequate resources to their real demands, especially in the university context, where specific practices are required to them, in relation to the production and promotion of academic texts. In this regard, this thesis aims to investigate how the mediating practices and the appropriation of the academic writing by students with disabilities are represented in their actions through the dimensions that constitute them. The interest in the study object of the present research is in line with researches developed in the Grupo de Estudos em Letramentos, Interação e Trabalho and in the Grupo de Pesquisa Agir de Linguagem, Docência e Educação Inclusiva, as well as with the actions of the Ateliê de Textos Acadêmicos project, which are based in the theoretical framework of the Sociodiscursive Interacionism (BRONCKART, 2012 [1999], 2006, 2008) and in its interdisciplinary theoretical basis, arising from the Linguistics with Saussure (1995), from the Psychology with Vygotsky (1991; 1993; 1997) and from the socio-philosophical approaches with Spinoza (2014 [1677], Ricoeur (1986) and Habermas (1987), as well as with the analytical categories proposed by the Action Semantics (BRONCKART; MACHADO, 2004; MACHADO; BRONCKART, 2009, BUENO, 2007) and some concepts related to the Work Clinic (CLOT, 2007 [1999]). For analysing the data, we identified, primarily, in the organizational plan of the text, the thematic contents and, next, in the semantics plan, we analysed the dimensions that constitute the action of the students with disabilities and of their mediators, considering the reasons, the intentionality and the resources that are situated in the investigative method proposed by the Action Semantics (BRONCKART; MACHADO, 2004; MACHADO; BRONCKART, 2009). The data generation of this qualitative research, with interpretative basis, was realized through interviews with supported and supporter students, both situated in the context of the activities realized by the Accessibility and Inclusion Committee for access, learning and permanence of students with disabilities in the university. The results show that the reading and writing practices are constituted as fundamental resources, in the plan of the Action Semantics, for the process of academic alphabetization of the supported student and, when they are satisfactorily mediated by the supporter students or the teachers, they contribute significantly to their inclusion in the disciplinary culture of the discursive community which they now integrate. Through the dimensions observed in the action of the diverse mediators involved in the process of appropriation of academic writing of the supported student, it is also possible to observe that they are directly related to their individual development, in the face of the affections that are produced (SPINOZA, 2014 [1677]) in the developed pedagogic mediation.